A coated and modified nickel-cobalt positive electrode material and preparation method thereof

By using the amino acid complex of aluminum mixed with the nickel-cobalt-manganese positive electrode material with microwave assistance and calcined under a low oxygen atmosphere to form a composite cladding layer of nitrogen-doped carbon and alumina, the problem of insufficient electrochemical performance of the nickel-cobalt-manganese positive electrode material is solved, and better cycle stability and rate performance are achieved.

CN115275169BActive Publication Date: 2025-03-14SHANDONG YAOMI NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211064932.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-01
Publication Date
2025-03-14
Estimated Expiration
2042-09-01

AI Technical Summary

Technical Problem

The electrochemical performance of existing nickel-cobalt-manganese ternary cathode materials has not yet met the need to improve, especially in terms of cycle stability and rate performance.

Method used

By using the amino acid complex of aluminum as the coating precursor, it is mixed with the nickel-cobalt-manganese positive electrode material under microwave-assisted conditions and calcined under a low oxygen atmosphere to form a composite cladding layer of nitrogen-doped carbon and alumina, effectively protecting the positive electrode material.

Benefits of technology

This method can significantly improve the cycle stability and rate performance of nickel-cobalt-manganese cathode material under thinner coating thickness, and the process is simple and does not require large and expensive equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115275169B_ABST
    Figure CN115275169B_ABST
Patent Text Reader

Abstract

The present invention relates to a coated modified nickel-cobalt positive electrode material, which is a composite coating layer of nitrogen-doped carbon and aluminum oxide, and the coated nickel-cobalt positive electrode material is expressed as NC-Al2O3@NCM, where NC-Al2O3 represents a composite coating layer of nitrogen-doped carbon and aluminum oxide, and NCM is a nickel-cobalt positive electrode material with a chemical formula of Li2Ni x Co y M z O2, wherein M is Mn and / or Al, x+y+z=1, and x≥0.5; the coating layer is a complex of amino acid and aluminum mixed with a nickel-cobalt-manganese cathode material under microwave-assisted conditions, and then calcined in a mixed atmosphere of oxygen and nitrogen; the volume content of oxygen in the mixed atmosphere is 5-15%, the calcination temperature is 600-900°C, and the calcination time is 30-50h. The strategy of coating the nickel-cobalt-manganese (aluminum) cathode material of the present invention can simultaneously improve the cycle stability and rate performance of the NCM cathode material; the coating modification method is simple and does not require complex large-scale equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion battery positive electrode materials, and in particular to a coated modified nickel-cobalt positive electrode material and a preparation method thereof. Background Art

[0002] Nickel-cobalt-manganese ternary positive electrode material (LiNixCoyMnzO2, x+y+z=1, NCM) is a new type of positive electrode material for lithium-ion batteries developed in recent years. It has important advantages such as high capacity, good cycle stability and moderate cost. Since this type of material can effectively overcome the problems of high cost of lithium cobalt oxide materials, low stability of lithium manganese oxide materials and low capacity of lithium iron phosphate, it has been successfully applied in batteries and its application scale has been rapidly developed. In the nickel-cobalt-manganese ternary positive electrode material, nickel, cobalt and manganese are adjusted within a certain range to obtain positive electrode materials with different performances. Currently, the more common ones are 333 (Ni, Co, Mn each account for 1 / 3), 523, 811 system, etc. However, the nickel-cobalt-manganese ternary positive electrode material still has some defects. In order to further improve the electrochemical properties of NCM materials, people further modify NCM materials. At present, the main modification methods include doping and coating. Cation doping can improve the stability of the electrode during the charge and discharge process of NCM materials, such as Al doping to obtain CNMA quaternary materials. There is also doping modification of metal cations such as Mg, Cu, and Ti, which improves the electrochemical performance of the material, reduces the cobalt content, and reduces the cost. However, doping requires the preparation of NCM materials from scratch, and the requirements for reaction conditions are relatively high, and it is impossible to process the existing commercially available NCM positive electrode materials. There is also a coating modification method, such as coating and modifying the NCM material with Al2O3, which improves the rate performance of the material. There is also a dispersion of AgNO3 and NCM precursors, and the solvent is dried and sintered to obtain a silver-coated CNM material, and the cycle stability is significantly better than that of the uncoated NCM. There is also AlF3 and Y2O3 for coating, which reduces the side reactions between the active substance and the electrolyte and enhances the stability of the positive electrode material. In general, the purpose of the coating modification treatment of NCM is to reduce the impact of lithium ion deintercalation on the crystal structure during the cycle, and to avoid the reaction between the material and the electrolyte.

[0003] The NCM positive electrode material coated and modified by electrochemical inert substances is currently widely studied. Because it is relatively easy to synthesize, it has good thermal stability and electrochemical stability, and is an ideal positive electrode material protective material. For example, the prior art uses metal oxides (Al2O3, ZrO2, TiO2, etc.), metal fluorides (MgF2, AlF3), and phosphates (such as iron phosphate) for coating. On the one hand, it is believed that the passivation layer of the metal oxide can organize the positive electrode active material to react with HF, and Al2O3 will preferentially react with HF, thereby reducing the dissolution of Co and Mn by HF. However, the electronic / ionic conductivity of the electrochemically inert material is low, which affects the rate performance of the positive electrode. If a dense and uniform electrochemically inert material coating layer with a thin coating layer thickness can be made, it can achieve protection of the positive electrode material while also having good electrochemical performance. There are currently reports on preparing ultra-thin coating layers by vapor phase chemical deposition and magnetron sputtering methods, but expensive and large equipment is required, which is not suitable for industrial large-scale production. The sol-gel method is a coating process that is currently being studied more. Since the material mixing and reaction are carried out in the liquid phase, uniform doping and / or coating can be achieved, but it consumes a large amount of solvent and has a long reaction time; pH, material concentration, material source, purity, etc. will affect the quality of the coating layer, and the process requirements are relatively strict, and it is also not suitable for large-scale industrial production. Although the above method cannot be used for actual commercial production, it provides a development direction for this type of material. Therefore, how to prepare a thin and dense coating layer through simple equipment and operation is of great scientific research significance and commercial value for NCM positive electrode materials, and even other types of positive electrode materials. Summary of the invention

[0004] In order to solve the problem that the electrochemical performance of nickel-cobalt-manganese ternary positive electrode materials in the prior art still needs to be improved, the present invention proposes a coated and modified nickel-cobalt positive electrode material, by adding an amino acid complex of aluminum as a coating layer precursor, under the action of microwave assistance, the coating layer is made uniform and dense, and can effectively protect the positive electrode material at a relatively thin coating layer thickness, while improving the cycle stability and rate performance of the positive electrode material. The method of the present invention does not require large and expensive equipment, nor does it require complicated operations. Commercially available nickel-cobalt-manganese (aluminum) positive electrode materials can be directly used as the raw materials to be coated, and the materials are mixed under microwave assistance, and then calcined to obtain a coated and modified nickel-cobalt ternary positive electrode material with excellent electrochemical performance.

[0005] The present invention achieves the above object through the following technical solutions:

[0006] A coated modified nickel-cobalt positive electrode material, characterized in that it is a composite coating layer of nitrogen-doped carbon and aluminum oxide, coated with a nickel-cobalt positive electrode material, expressed as NC-Al2O3@NCM, NC-Al2O3 represents a composite coating layer of nitrogen-doped carbon and aluminum oxide, NCM is a nickel-cobalt positive electrode material, and the chemical formula is Li2Ni x Co y M z O2, wherein M is Mn and / or Al, x+y+z=1, and x≥0.5; the coating layer is a complex of amino acid and aluminum mixed evenly with a nickel-cobalt-manganese positive electrode material under microwave-assisted conditions, and then calcined in a mixed atmosphere of oxygen and nitrogen; the volume content of oxygen in the mixed atmosphere is 5-15%, the calcination temperature is 600-900°C, and the calcination time is 30-50h.

[0007] The nickel-cobalt positive electrode material described in the present invention includes, in addition to the conventional nickel-cobalt-manganese ternary positive electrode material (NCM), other ternary or multi-element positive electrode materials that are doped or replaced with metal elements, such as nickel-cobalt-aluminum (NCA) ternary positive electrode and nickel-cobalt-manganese-aluminum quaternary positive electrode (NCMA).

[0008] Preferably, the coating layer is a complex of amino acid and aluminum mixed with nickel-cobalt-manganese positive electrode material under microwave-assisted conditions and then calcined in a mixed atmosphere of oxygen and nitrogen. The volume content of oxygen in the mixed atmosphere is 5-15%, the calcination temperature is 600-900°C, and the calcination time is 30-50h; preferably, the volume content of oxygen in the mixed atmosphere is 8-12%. The present invention chooses to sinter in an atmosphere with an oxygen content of 8-12% because if calcined directly in the air or in an atmosphere with an oxygen content higher than 12%, the N on the amino acid in the ligand will react to NO x The inventors found that calcination under low oxygen concentration will produce a composite coating layer of nitrogen-doped carbon and aluminum oxide, which significantly improves the electrochemical performance of the NCM positive electrode material. It may be that part of the N has a good affinity with the metal of the NCM material through coordination, and forms a certain solid solution during the calcination process to produce nitrogen-doped carbon, which increases the graphitization degree of the carbon layer, enhances the conductivity, and makes the carbon layer structure more stable, thereby stabilizing the NCM crystal structure and increasing its surface ion / electron diffusion rate; the formation of a dense aluminum oxide coating is conducive to stabilizing the crystal structure of the NCM material, making it more stable while not affecting its electrochemical activity; during calcination, the oxygen concentration cannot be higher than 12%, otherwise the N element will form nitrogen oxides (NO x) escapes from the system too early, which is not conducive to the formation of a uniform and dense coating layer. The oxygen concentration cannot be too low, otherwise a dense alumina coating layer cannot be effectively obtained. The core idea of ​​the present invention is to make use of the affinity of the amino acid ligand for the NCM material to make the coating layer produced during the calcination process under a low-oxygen atmosphere more uniform and dense, the interface contact with the NCM crystal is closer, the structure is more complete, and the defect rate is reduced. In this way, effective protection of the NCM positive electrode material can be achieved under the condition of a thinner coating thickness, and the electrochemical properties of the positive electrode material, especially the rate performance, can be improved. If the calcination temperature is too high, the calcination time is too long, or the oxygen content in the atmosphere is high during calcination, the above effect cannot be achieved.

[0009] Furthermore, the amino acid is not particularly limited, and conventional amino acids in the art may be used, such as at least one selected from glycine, alanine, leucine, valine, serine, and tryptophan, preferably tryptophan. In addition to the primary amino group, tryptophan also has NH on the indole, which can provide better affinity with the NCM positive electrode material.

[0010] The prior art generally selects alkyl alcohol metals (such as aluminum isopropoxide, n-butoxide, etc.) as the precursor of the metal oxide coating layer, such as the patent. However, after long-term research, it is found that the alkyl alcohol metal needs to be mixed with a nickel-cobalt-manganese precursor (generally a solution of nickel salt, cobalt salt, and manganese salt) in the presence of an alkali solution and a complexing agent to obtain a precursor, and then the precursor is mixed with a lithium source (generally lithium hydroxide or lithium carbonate) in a certain equivalent ratio for calcination to finally obtain a metal oxide-coated NCM positive electrode material. However, due to the poor affinity between the alkyl alcohol metal and the NCM precursor, even if the NCM precursor is obtained by a coprecipitation reaction in a homogeneous solution, the oxide coating layer will still have some defects during the sintering process. In order to achieve the protective effect of the positive electrode material on the electrolyte, the coating layer needs to be made relatively thick, but the thicker coating layer will hinder the rate performance of the CNM positive electrode material. The present invention selects an amino acid complex of aluminum as a precursor of a coating layer of alumina, and mixes the materials under microwave-assisted conditions. A commercially available NCM positive electrode material can be directly used as a raw material, and the mixed product of NCM and the precursor is calcined in a low-oxygen atmosphere, so that alumina is uniformly and densely coated on the surface of the NCM positive electrode material, and the alumina may have a certain amount of N doping. At the same time, the nitrogen-containing organic ligand in the precursor is converted into nitrogen-doped carbon with a high degree of graphite, good conductivity and excellent mechanical properties after calcination, which is more conducive to improving the electrochemical performance of the NCM positive electrode material.

[0011] Preferably, in the coating layer, the atomic proportions of the elements are: Al accounts for 48-53%, O accounts for 43-46%, C accounts for 3-7%, and N accounts for 0.4-1.5%.

[0012] Preferably, the coating layer has a thickness of 2-10 nm, preferably 5-7 nm.

[0013] The second object of the present invention is to provide a method for preparing the above-mentioned coated modified nickel-cobalt positive electrode material, comprising the following steps:

[0014] (S1) the amino acid and the aluminum salt are uniformly mixed in an organic solvent, heated under reflux for 2-3 days in an inert atmosphere, filtered, washed, and dried to obtain an aluminum amino acid complex;

[0015] (S2) dispersing the crushed nickel-cobalt positive electrode material in an organic solvent, adding the amino acid complex of aluminum obtained in step (S1), stirring under microwave-assisted conditions to fully mix the materials, and centrifugally drying them for later use;

[0016] (S3) calcining the dried material in step (S2) in a mixed atmosphere of nitrogen and oxygen, wherein the volume content of oxygen in the mixed atmosphere is 8-12%, the calcination temperature is 600-900° C., and the calcination time is 30-50 hours.

[0017] Further, in step (S1), the amount of amino acid added is 2.5-4 times the amount of aluminum salt. Generally, amino acid and metal salt form a complex at a ratio of 2:1. In step (S1), the amount of amino acid added is excessive to make the coordination more complete. The amount of solvent used is not particularly limited, as long as it can fully disperse the materials, and is generally 10-15 times the mass of amino acid and aluminum salt.

[0018] Furthermore, in step (S1), the inert atmosphere is nitrogen and / or argon, and in step (S1) and step (S2), the organic solvent is at least one of anhydrous methanol, anhydrous ethanol, anhydrous acetone, and anhydrous acetonitrile. Preferably, in step (S2), the solvent is anhydrous acetonitrile. In step (S2), since NCM positive electrode materials are involved, they are relatively stable in aprotic solvent environment.

[0019] Furthermore, the crushing method in step (S2) is not particularly limited, such as ball milling, air flow milling, etc. The purpose of crushing is to make the D50 of the nickel-cobalt-manganese ternary positive electrode material 8-15μm. Preferably, the particle size distribution of the nickel-cobalt positive electrode material is D10>4.5μm, D50 is 9-12μm, D90<16μm, and D100<30μm.

[0020] Furthermore, in step (S2), the crushed nickel-cobalt positive electrode material is dispersed in an organic solvent, the mass concentration of the nickel-cobalt positive electrode material is 15-20wt%, and the amount of the aluminum amino acid complex added is 8-12wt% of the nickel-cobalt-manganese ternary positive electrode material.

[0021] Furthermore, in step (S2), microwave assistance means that the microwave frequency is 500-600 MHz and the power is 200-300 W. The applicant has found that under microwave assistance, the affinity between the amino acid complex precursor of aluminum and the NCM positive electrode material is enhanced, which is more conducive to obtaining a uniform and dense coating layer.

[0022] Furthermore, in step (S2), the process conditions and steps of stirring and mixing, centrifugation and drying are well known in the art. In a specific embodiment of the present invention, the stirring is at a speed of 300-500 rpm, the stirring time is 20-30 hours, the centrifugation is at a speed of 5000-10000 rpm for 1-2 hours, the supernatant is poured out, and the lower layer of solid is taken out and vacuum dried at 60-80°C and 0.05-0.1MPa.

[0023] Further, the calcination of step (S3) is calcined in stages, firstly, the temperature is raised to 600-650°C at 15-20°C / min, and the temperature is kept for 15-20h, then the temperature is raised to 800-900°C at a heating rate of 5-10°C / min, and the temperature is kept for 12-15h, and finally the temperature is lowered and sintered, and the cooling rate is 5-10°C / min, and the temperature is lowered to 580-630°C, and the temperature is kept for 3-5h. The present invention weakens the surface activity of the material through a staged heating and a cooling program calcination process, which is conducive to the coating layer being evenly and densely coated on the NCM positive electrode material.

[0024] The third object of the present invention is to provide a lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the active material of the positive electrode comprises the above-mentioned coated and modified nickel-cobalt positive electrode material.

[0025] Compared with the prior art, the present invention has achieved the following technical advances:

[0026] 1. Nickel-cobalt-manganese (aluminum) positive electrode materials have structural collapse, oxygen evolution reaction, dissolution of metal elements such as Mn and Co, and side reactions with the electrolyte during the long cycle of lithium batteries, which leads to increased battery impedance and decreased cycle performance. Coating and modification of NCM positive electrode materials can overcome the above defects to a certain extent. However, when coating electrochemically inert substances, the coating layer is not uniform and dense enough due to the imperfect preparation process, resulting in a decrease in the rate performance of NCM. The present invention uses an amino acid complex of aluminum as a coating layer precursor and calcines it in an oxygen atmosphere of 8-12 vol% to obtain a thin and uniformly dense coating layer, which protects the NCM positive electrode material, improves the cycle stability, and also improves the rate performance of the NCM material.

[0027] 2. The present invention heats up in stages to 600-650°C and 800-900°C, and then cools down for heat preservation treatment, so as to obtain a more uniform and dense coating layer with optimal cycle performance and coating performance.

[0028] 3. The coating strategy of the present invention for nickel-cobalt-manganese (aluminum) positive electrode materials can simultaneously improve the cycle stability and rate performance of NCM positive electrode materials. At the same time, the coating modification method of the present invention is simple, does not require complex large-scale equipment, and can directly coat the nickel-cobalt-manganese (aluminum) positive electrode materials without starting synthesis from NCM precursors. The coating strategy of the present invention is not only applicable to nickel-cobalt-manganese (aluminum) positive electrode materials, but also to other positive electrode materials, such as lithium cobalt oxide, lithium iron phosphate, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a SEM photo of the uncoated NCM cathode material;

[0030] Figure 2 is a SEM photograph of the coated and modified NCM positive electrode material obtained in Example 1;

[0031] Figure 3 This is a TEM photo of the coated and modified NCM positive electrode material obtained in Example 1;

[0032] Figure 4 This is the XRD diagram of the coated and modified NCM positive electrode material obtained in Example 1. DETAILED DESCRIPTION

[0033] The present application is further described below by way of examples.

[0034] NCM cathode material Li2Ni 0.5 Co 0.2 Mn 0.3 O2 was purchased from Sichuan New Lithium Energy Technology Co., Ltd., product batch number XLXK100FP22, impurity LiCO3≤1400ppm, LiOH≤900ppm, particle size distribution of D10>4.5μm, D50 9-12μm, D90<16μm, D100<30μm.

[0035] Example 1

[0036] (S1) adding tryptophan and aluminum chlorotrihydrate to anhydrous ethanol, wherein the amount of tryptophan is 3.2 times that of aluminum chlorotrihydrate, and the amount of anhydrous ethanol is 10-15 times the total mass of tryptophan and aluminum chlorotrihydrate, mixing them evenly under stirring, heating under reflux for 2 days under a nitrogen atmosphere, filtering, washing, and drying to obtain an aluminum amino acid complex;

[0037] (S2) NCM positive electrode material (Li2Ni 0.5 Co 0.2 Mn 0.3O2) dispersed in anhydrous acetonitrile to make NCM mass concentration of 3.8wt%, added with the aluminum amino acid complex obtained in step (S1), the amount of aluminum amino acid complex added is 10wt% of NCM positive electrode material, under the auxiliary conditions of microwave frequency 500MHz and microwave power 300W, the materials are mixed at a stirring speed of 400rpm for 24h, mixed evenly, centrifuged at 700r0pm for 1h, poured out the supernatant, took out the powder, and vacuum dried at 80℃ and 0.05MPa for standby use;

[0038] (S3) The dried material in step (S2) is calcined in stages under a mixed atmosphere of nitrogen and oxygen (oxygen volume content is 8%). The first heating stage: heating to about 600°C at a heating rate of 15°C / min and keeping warm for 20 hours; the second heating stage: heating to 800°C at a heating rate of 10°C / min and keeping warm for 15 hours; the cooling stage: cooling to 600°C at a cooling rate of 10°C / min and keeping warm for 5 hours, and then naturally cooling to room temperature to obtain the coated modified NCM positive electrode material.

[0039] Figure 1 This is a SEM photo of the uncoated NCM positive electrode material.

[0040] Figure 2 This is a SEM photograph of the coated and modified NCM positive electrode material obtained in Example 1.

[0041] Figure 3 This is a TEM photograph of the coated and modified NCM positive electrode material obtained in Example 1. It can be seen that the thickness of the coating layer is about 5-7nm.

[0042] Figure 4 This is the XRD diagram of the coated and modified NCM positive electrode material. It can be seen that after coating and modification, there is no effect on the lattice of the NCM positive electrode material.

[0043] Through the mapping of the projection electron microscope photos, it can be seen that the Al and O elements of the coating layer are evenly distributed in the coating layer, and the atomic proportions are 48.65% Al, 43.29% O, 1.22% N, and 6.84% C.

[0044] Example 2

[0045] Other conditions and operations are the same as those in Example 1, except that in step (S2), the amount of the amino acid complex of aluminum added is 12wt% of the NCM positive electrode material. In the coating layer, the atomic proportions are 48.86% Al, 43.47% O, 1.16% N, and 6.51% C.

[0046] Example 3

[0047] Other conditions and operations are the same as those in Example 1, except that in step (S3), the nitrogen and oxygen mixed atmosphere has an oxygen content of 12% by volume. In the coating layer, the atomic ratios are 51.08% Al, 45.44% O, 0.45% N, and 3.03% C.

[0048] Example 4

[0049] Other conditions and operations are the same as those in Example 1, except that in step (S3), the nitrogen and oxygen mixed atmosphere has an oxygen content of 5% by volume. In the coating layer, the atomic percentages are 52.12% Al, 41.57% O, 0.96% N, and 5.35% C.

[0050] Example 5

[0051] Other conditions and operations are the same as those in Example 1, except that in step (S3), the calcination is as follows: the first heating stage: heating to about 650°C at a heating rate of 15°C / min, and keeping warm for 15 hours; the second heating stage: heating to 900°C at a heating rate of 10°C / min, and keeping warm for 12 hours; the cooling stage: cooling to 630°C at a cooling rate of 10°C / min, and keeping warm for 5 hours.

[0052] Example 6

[0053] Other conditions and operations are the same as those in Example 1, except that in step (S3), the calcination is performed at 600° C. for 50 h.

[0054] Example 7

[0055] Other conditions and operations are the same as those in Example 1, except that in step (S3), the calcination is performed at 900° C. for 40 h.

[0056] Example 8

[0057] Other conditions and operations were the same as those in Example 1, except that in step (S1), the amino acid was replaced by glycine from tryptophan.

[0058] Comparative Example 1

[0059] Other conditions and operations are the same as those in Example 1, except that step (S1) is eliminated and aluminum n-propoxide is used as a precursor of the coating layer in step (S2).

[0060] Comparative Example 2

[0061] Other conditions and operations are the same as those in Example 1, except that in step (S2), the microwave-assisted operation is cancelled.

[0062] Application Examples

[0063] The positive electrode materials of the above embodiments and comparative examples, SuperP and PVDF were prepared into positive electrode slurry at a ratio of 8:1:1, coated on a copper foil current collector to make a positive electrode, the negative electrode was a metal lithium sheet, the separator was a commercially available polypropylene separator, the electrolyte was lithium hexafluorophosphate (1 mol / L), and the electrolyte solvent was a mixed solvent of dimethyl carbonate and diethyl carbonate at a volume ratio of 1:1 to make a 2032 button battery. At 25°C, the charge and discharge range of 3.0V-4.3V was tested for charge and discharge. The results are shown in Table 1 below:

[0064] Table 1

[0065]

[0066] It can be seen that the coated and modified nickel-cobalt-manganese cathode material of the present invention, compared with the conventional aluminum oxide coating, can obtain a composite coating layer of nitrogen-doped carbon and aluminum oxide by sintering in an atmosphere with a lower oxygen content due to the use of an aluminum amino acid complex as an aluminum source, which has advantages in the electrochemical performance of NCM cathode materials, especially in high-rate electrochemical performance.

Claims

1. A coated and modified nickel-cobalt positive electrode material, characterized in that: It is a composite coating of nitrogen-doped carbon and aluminum oxide, coated with nickel-cobalt positive electrode material, expressed as NC-Al2O3@NCM, NC-Al2O3 represents a composite coating of nitrogen-doped carbon and aluminum oxide, NCM is a nickel-cobalt positive electrode material, the chemical formula is Li2Ni x Co y M z O2, wherein M is Mn and / or Al, x+y+z=1, and x≥0.5; the volume content of oxygen in the mixed atmosphere is 8-12%, the calcination temperature is 600-900°C, and the calcination time is 30-50h; The coated modified nickel-cobalt positive electrode material is prepared by a preparation method comprising the following steps: (S1) the amino acid and the aluminum salt are uniformly mixed in an organic solvent, heated under reflux for 2-3 days under an inert atmosphere, filtered, washed, and dried to obtain an amino acid complex of aluminum; the amino acid is selected from at least one of glycine, alanine, leucine, valine, serine, and tryptophan; the amount of the amino acid added is 2.5-4 times the amount of the aluminum salt; (S2) dispersing the crushed nickel-cobalt positive electrode material in an organic solvent, adding the amino acid complex of aluminum obtained in step (S1), stirring under microwave-assisted conditions to fully mix the materials, and centrifugally drying them for later use; (S3) calcining the dried material in step (S2) in a mixed atmosphere of nitrogen and oxygen, wherein the volume content of oxygen in the mixed atmosphere is 8-12%, the calcination temperature is 600-900° C., and the calcination time is 30-50 hours.

2. The coated and modified nickel-cobalt positive electrode material according to claim 1, characterized in that: In the coating layer, the atomic proportions of each element are: Al accounts for 48-53%, O accounts for 43-46%, C accounts for 3-7%, and N accounts for 0.4-1.5%.

3. The coated and modified nickel-cobalt positive electrode material according to claim 1, characterized in that: The thickness of the coating layer is 5-7 nm.

4. The coated and modified nickel-cobalt positive electrode material according to claim 1, characterized in that: In step (S2), the crushed nickel-cobalt positive electrode material is dispersed in an organic solvent, the mass concentration of the nickel-cobalt positive electrode material is 15-20wt%, and the amount of the aluminum amino acid complex added is 8-12wt% of the nickel-cobalt positive electrode material.

5. The coated and modified nickel-cobalt positive electrode material according to claim 1, characterized in that: In step (S2), microwave assistance means that the microwave frequency is 500-600 MHz and the power is 200-300 W.

6. The coated and modified nickel-cobalt positive electrode material according to claim 1, characterized in that: The calcination in step (S3) is carried out in stages. First, the temperature is increased to 600-650°C at a rate of 15-20°C / min, and kept at this temperature for 15-20 hours. Then, the temperature is increased to 800-900°C at a rate of 5-10°C / min, and kept at this temperature for 12-15 hours. Finally, the temperature is reduced and sintered at a rate of 5-10°C / min to 580-630°C, and kept at this temperature for 3-5 hours.

7. A lithium-ion battery comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the active material of the positive electrode comprises the coated and modified nickel-cobalt positive electrode material according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Surface coating method of lithium ion battery positive electrode material based on microwave assistance

    CN111082060A

  • Preparation method of Al2O3-coated NCM ternary positive electrode material

    CN112635740A